Antioxidant Activity Test of Ethanol Extract of Andaliman Fruit (Zanthoxylum Acanthopodium DC.) on Superoxide Dismutase (SOD) Levels in Rats - Arsiaty; Yulia Delfahedah; Andre Bastian Manik; Nurasima Kurniati Damanik (International Journal of Public Health Excellence (IJPHE), 2022)
Free radicals are compounds or molecules that contain one or more unpaired electrons in their outer orbitals. If the production of free radicals is excessive, it can cause oxidative damage which ends in cell death resulting in the acceleration of various degenerative diseases. To neutralize the work of free radicals, external antioxidants are needed. Andaliman (Zanthoxylum acanthopodium DC) is a source of natural antioxidants that contain flavonoids that can neutralize free radicals. This research included sample preparation, examination of simplicia characteristics, screening of simplicia phytochemicals, extract preparation, determination of SOD activity spectrophotometrically using reagents. A total of 30 rats were divided into 6 groups consisting of the control group, the stress-induced group, the comparison group, and the three stress-induced and EEBA groups with doses of 75 mg/kg, 150 mg/kg, and 300 mg respectively. /kg bw. Stress induction was carried out by administering EEBA for 7 days and continued by administering EEBA together with doxorubicin for the next 2 days. The results showed that the average SOD level in the control group was (4.626 0.2583), the doxorubicin group (1.956+ 0.0879), the EEBA group 75 mg kg body weight (2.444 0.0844), the EEBA group 150 mg/kg body weight ( 3.052 +0.1139), the EEBA 300 mg/kg body weight (3.646+0.1739) and the Routine 50 mg/kg body weight 5.594 + 0.2056), EEBA had higher SOD activity when compared to the doxorubicin group. Based on the statistical results, SOD activity increased with the increase in the dose of EEBA given and showed a significant difference (p<0.05) between the EPBA group and the doxorubicin group. Observations on liver tissue in the group given EEBA showed better conditions than the liver in the doxorubicin group.